Acanthephyra brevirostris Smith 1885 - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Acanthephyra brevirostris Smith, 1885 A near-cosmopolitan, bathypelagic species in tropical and temperate waters (Kensley 1968) reaching the sub- Antarctic Region near Marion Island (Spence Bate 1888 as Hymenodora duplex Spence Bate, 1888). Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 217, DOI:10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302